Neurodevelopmental origin and adult neurogenesis of the neuroendocrine hypothalamus - Maggi, Roberto; Zasso, Jacopo; Conti, Luciano (Frontiers in Cellular Neuroscience, 2015)
The adult hypothalamus regulates many physiological functions and homeostatic loops, including growth, feeding and reproduction. In mammals, the hypothalamus derives from the ventral diencephalon where two distinct ventricular proliferative zones have been described. Although a set of transcription factors regulating the hypothalamic development has been identified, the exact molecular mechanisms that drive the differentiation of hypothalamic NPCs toward specific neuroendocrine neuronal subtypes is yet not fully disclosed. Neurogenesis has been also reported in the adult hypothalamus at the level of specific niches located in the ventrolateral region of ventricle wall, where NPCs have been identified as radial glia-like tanycytes. Here we review the molecular and cellular systems proposed to support the neurogenic potential of developing and adult hypothalamic NPCs. We also report new insights on the mechanisms by which adult hypothalamic neurogenesis modulates key functions of this brain region. Finally, we discuss how environmental factors may modulate the adult hypothalamic neurogenic cascade.